Comparison of cell disruption methods for improving lipid extraction from Porphyridium cruentum - Pintaka Kusumanintyas; Muhammad Nashir; Maria Emilia Inda; Anggun Noor Kurnia Sari; Mery Fazria Setya Rahayu; Marselina Dau (Bivalen: Chemical Studies Journal, 2021)
Cell disruption and extraction processes are very important downstream processing steps in microalgae-based in industrial bioprocesses. Each type of microalgae has a varied cell wall structure, so it is necessary to optimize an effective and economical cell disruption method to maximize the extraction process. This study aimed to evaluate several cell disruption methods, including: osmotic shock method (NaCl 20% w/v), acid method (HCl 3M), and microwave (450W, 5 min) for lipid extraction for Porphyridium cruentum biomass. Lipid extraction was carried out using n-hexane as solvent. Among several tested methods, the highest yield of lipid extraction was obtained by using acid method (8.15 ± 0.12% w/w), while the microwave method only produced lipids of 2.79 ± 0.37% w/w, and the lowest yield was obtained by using osmotic shock (1.07 ± 0.44 % w/w). The acid method is a very simple method for disruption of P. cruentum cells, because it does not involve the use of expensive equipment. Therefore, this method is considered efficient and economical for use in the extraction process of lipid or other biomolecule compounds.